Konstruksi Sosial Terhadap Identitas Kultural Masyarakat Suku Tengger Ngadas Dalam Menanggapi Formalisasi Agama - ului, noviati; Sudrajat, Arief (Paradigma, 2024)
This research aims to understand how the Tengger Ngadas community deals with the formalization of Islam and its impact on their cultural identity as Hindus. It was conducted with the aim of providing insights to the government and non-governmental organizations to design more inclusive and sustainable policies. A qualitative method with Peter L. Berger's social construction theory approach was used to observe the phenomenon in Ngadas Village, Poncokusumo District, Malang Regency. The results showed that the formalization of Islam affected the religious practices, cultural values, and collective identity of the Ngadas Tengger community, creating value conflicts with long-held Hindu traditions. Nevertheless, the Ngadas Tengger community continues to strive to maintain their cultural identity by adjusting and reinterpreting cultural values in the context of Islam. The conclusion of this study shows that religious formalization has changed the social identity of the Tengger people as a response to the state's efforts to reduce the nationalist movement. Despite the conflict, the Tengger community seeks to accommodate religious formalization, which results in a change of identity to Tengger Hinduism through acculturation, assimilation, and syncretism. This process is part of the externalization of Tengger identity, which starts from strengthening identity to transitioning into Tengger Hinduism, then giving birth to a new identity through objectivation. Tengger Hindu identity remains vulnerable to change, reflecting the dialectical cycle of social reality. Internalization allows social institutions to socialize Tengger Hindu identity to the younger generation. Keywords: Construction, Cult Identity, Religious Formalization